P305 ACUTE MYOPERICARDITIS IN 2021: COVID19 RELATED?. (18th May 2022) - Pasquero, M; Ruffini, S; Astegiano, M; Franco, E; Moretti, C
Abstract: The term myopericarditis is used when there are primarily pericarditis symptoms with myocardium involvement as evidenced by cardiac biomarker elevation or imaging studies revealing normal wall motion. We report a case of a young 23–years old man, who presented to the Emergency Department with fever and diarrhea lasting 5 days followed by acute chest pain, modified by trunk position. The electrocardiogram (ECG) showed diffuse inferior and anterolateral ST–segment elevation. No signs of hemodynamic instability were detected. Laboratory tests showed WBC 8840/mmc, CRP 53, 2 mg/L, TnT 986 ng/L, a mildly altered liver function with AST 92 UI/L, ALT 88 UI/L, GGT 82 UI/L and an altered pancreatic function with amylase 190 UI/L, lipase 267 UI/L. Naso–pharyngeal swab was negative. The patient received COVID–19 mRNA vaccination 4 months before symptoms, with high immune response, detected with IgG dosage (465 BAU/ml). Ecocardiography showed a left ventricle with normal size, function, and segmental contractility. Valvular apparatus in normal range. Hyper–refraction of the posterior pericardium with minimal effusion. The diagnosis of acute myopericarditis was glaring and we treated the patient with high dosage of non–steroidal anti–inflammatory drugs, colchicine and ACE Inhibitors, based on the increased troponin levels (nadir 1439 nl/L), in order to prevent the possible cardiovascular remodeling. On laboratory testing, the deepening of the main causes of viral or autoimmune myopericarditis did not clarify the etiopathogenesis. No arrhythmias occurred on ECG monitoring. Cardiac MRI showed multiple areas of altered signal (T2) and altered uptake in lateral and inferior ventricular segments and in adjacent pericardium. The pain was gone in two days and left ventricle function was still preserved upon discharge. In conclusion we report a successful treatment of acute myopericarditis of unknown pathogenesis, in a healthy young man. As there are described cases of myopericarditis and myositis associated with COVID–19 in the absence of respiratory symptoms, and others related to SARSCoV2 mRNA vaccination, we dutifully excluded both.